40 years of Populorum Progressio: a political reading (Cultura Económica, 2019)
As its title indicates, the article by Professor Julio M. Ojea Quintana is an analysis of the political dimension of the encyclical Populorum Progressio. After some clarification regarding the historical context of the writing of the Papal document, the author examines the perspective from which the political issues included in the encyclical are considered.Among these, the article refers specifically to the common good, the role of politics and authority in relation to the principle of subsidiarity, and revolutionary violence.
Keywords: Populorum Progressio; context; genesis; common good; democracy